DISSERTATIONAL RESEARCH: A SURVEY AND CREATIVE INTERVENTION - Bitinas, Bronislovas (Acta Paedagogica Vilnensia, 2011)
The article focuses on discussion of methodological requirements for the research conducted by a doctoral student, which is the main quality indicator of doctoral thesis. Though such research is usually carried out following contemporary research methodology, additional methodological requirements are established for a doctoral thesis because the novelty and theoretical significance of the theme of the doctoral thesis and defended statements are evaluated officially. The topicality of the research theme is a primary task of every Doctoral student; a novice researcher needs support of an experienced scientist. The theme is considered to be topical, if: 1) the research object really exists and is worth cost of research work allotted to its cognition; 2) the research problem is sufficiently substantiated; 3) a doctoral student is capable to develop the research design, which may ensure a solution to the established problem. The novelty of the research results is identified at the end of the research and three levels of such novelty may be pointed out. Novel conclusions at concretisation level are the ones, which concretise statements of education theory under conditions of a separate country; conclusions at supplement level specify, expand statements of the theory or practical activity, whose certain aspects were analysed by a researcher; doctoral students strive for novelty of conclusions at conceptual level very rarely. Theoretical significance of results is evaluated following the proposition that a conclusion made by a researcher may be referred to as scientific result only when this conclusion may find its place in the system of previously proved scientific statements and research conclusions. The education parameters defined in the article (education as interaction between an educator and a learner, information and stochastic processes) implicate a conclusion that quantitative and qualitative researches, regardless of their differences, actually supplement each other. On the other hand, such strategies realise observational cognition of education, which may be contrasted to the researcher‘s activity aimed of improving the research object (interventional cognition). In the process of studies it is important to encourage doctoral students to conduct interventional researches and to include them into the design of their dissertational research. The question arises how to combine application of interventional and observational strategies in dissertation research. Classical experiment is methodologically substantiated best but it is not a typical method of dissertational research; one-alternative and model experiments are more frequently applied in reality as well as education projects and activity research. The essence of the project embraces the search for or creation of new (or at least relatively new but topical) education components; such variant of educational process is created under researcher‘s initiative and by joint efforts of education and its participants. Research on activity strategy refers to theoretical actualisation of educational activity; it acquires scientific nature, when it is based on the principle to research while performing and perform while conducting research. Generalising, it can be concluded that the content of scientific methodological training of doctoral students in educational science should also implicate training of doctoral students to employ a trinomial methodological system, which consists of application of interventional, qualitative and quantitative strategies, on the basis of the chosen scientific problem.